2017
DOI: 10.1016/j.vaccine.2017.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanting an inactivated influenza vaccine with conjugated R848 improves the level of antibody present at 6 months in a nonhuman primate neonate model

Abstract: Generation of a potent antibody response that can be sustained over time is highly challenging in young infants. Our previous studies using a nursery-reared nonhuman primate model identified R848 conjugated to inactivated influenza virus as a highly immunogenic vaccine for neonates. Here we determined the effectiveness of this vaccine in mother-reared infants as well as its ability to promote improved responses at 6 months compared to vaccination in the absence of R848. In agreement with our nursery study, R84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(47 reference statements)
1
19
1
Order By: Relevance
“…We chose the TLR7/8 agonist 3M-052 because TLR7/8 agonists are uniquely able to activate neonatal and infant APCs (2,9). Indeed, our results demonstrated that the highest breadth and functionality were observed when infant macaques were vaccinated with the 3M-052-SE-adjuvanted Env protein (38,39). Our finding that 3M-052-SE outperformed GLA-SE is consistent with previous studies documenting the potency of TLR7/8-based adjuvants for pediatric vaccines.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We chose the TLR7/8 agonist 3M-052 because TLR7/8 agonists are uniquely able to activate neonatal and infant APCs (2,9). Indeed, our results demonstrated that the highest breadth and functionality were observed when infant macaques were vaccinated with the 3M-052-SE-adjuvanted Env protein (38,39). Our finding that 3M-052-SE outperformed GLA-SE is consistent with previous studies documenting the potency of TLR7/8-based adjuvants for pediatric vaccines.…”
Section: Discussionsupporting
confidence: 86%
“…Our finding that 3M-052-SE outperformed GLA-SE is consistent with previous studies documenting the potency of TLR7/8-based adjuvants for pediatric vaccines. This includes the aforementioned vaccination of neonatal macaques with PCV in the absence and presence of 3M-052 (15) and a study in which infant macaques vaccinated with an inactivated influenza vaccine conjugated to the TLR7/8 agonist R848 developed enhanced and sustained antibody responses compared to responses of infants receiving unadjuvanted vaccine (38,39). In contrast to alum or oil-in-water emulsions like MF59, adjuvants based on or incorporating TLR ligands can directly activate innate responses and thereby improve priming and the induction of adaptive immune responses by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The same vaccination schedule was used for groups receiving R848 as the “gold standard” adjuvant that has been extensively used to promote neonatal immunity [ 34 , 35 , 36 ]. Although R848 has been claimed to elicit potent immunity when used in neonates [ 35 , 37 , 38 , 39 , 40 ], we found that in our experimental setting the use of R848 did not significantly increase the frequency of multifunctional T cells expressing IFN-γ, TNF-α, and IL-2. Moreover, the presence of CD4 + T cells that produce any possible combination of the four analyzed cytokines (IFN-γ, TNF-α, IL-17, and IL-2) was indeed reduced when a neonatal dose of R848 was used as compared to the treatment where this dose was skipped or in adult controls ( Figure 2 A).…”
Section: Resultscontrasting
confidence: 63%
“…152 This and follow up studies demonstrated the Resiquimodinfluenza conjugate vaccine generated efficacious influenza immunity in non-human primate neonates, a difficult vaccination model. 153,154 These studies highlight both the clinical potential of TLR7/8 agonist conjugates and the need to development site-specific methods for agonist conjugation to improve antigen-specific immune responses while preserving antigen recognition.…”
Section: ø Tlr7 and Tlr8mentioning
confidence: 99%